2017
DOI: 10.21873/anticanres.11412
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Human Oral Keratinocyte by Doxorubicin

Abstract: Abstract. Background For the exploration of new anticancer drugs, experiments with tumor-bearing animals are mandatory. However, the results obtained with animals have to be carefully evaluated, since drug metabolisms are quite different between animals and humans (1, 2). The other approach is to use cell cultures that mimic whole body. We have established an in vitro assay method of anti-tumor activity, based on the relative cytotoxicity against human oral squamous cell carcinoma (OSCC) cell lines (Ca9-22, HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 10 publications
5
34
0
Order By: Relevance
“…SE, a group of three over-the-counter drugs, showed the highest neuroprotective activity against both undifferentiated and differentiated PC12 cells, as well as undifferentiated SH-SY5Y cells. This seems to be linked to growth stimulation at lower doses, known as hormesis [ 40 ], since we have experienced similar growth stimulation of SE towards human gingival epithelial fibroblast (HGEP) [ 41 ] and PC12 cells [ 33 ]. SE showed prominent anti-HIV [ 42 ] and anti-UV activity [ 43 ], like the lignin-carbohydrate complexes extracted with alkaline solution.…”
Section: Discussionmentioning
confidence: 99%
“…SE, a group of three over-the-counter drugs, showed the highest neuroprotective activity against both undifferentiated and differentiated PC12 cells, as well as undifferentiated SH-SY5Y cells. This seems to be linked to growth stimulation at lower doses, known as hormesis [ 40 ], since we have experienced similar growth stimulation of SE towards human gingival epithelial fibroblast (HGEP) [ 41 ] and PC12 cells [ 33 ]. SE showed prominent anti-HIV [ 42 ] and anti-UV activity [ 43 ], like the lignin-carbohydrate complexes extracted with alkaline solution.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that classical anticancer drugs exerted both good effect [extremely higher cytotoxicity against human oral squamous cell carcinoma (OSCC) cell lines than human normal oral mesenchymal cells], and bad effect (potent cytotoxicity against human normal oral epithelial cells) (2,3). Recently, moleculartargeted drugs, such as cetuximab (Cmab) and nivolumab (Nmab) have been approved for the treatment of head and neck cancer in Japan (November 10, 2016).…”
mentioning
confidence: 99%
“…showed higher TS and PSE values, than [1][2][3][4][5][6][7] and [15][16][17][18][19][20][21]. The most active compound [8][9][10][11][12][13][14] induced apoptosis in C9-22 OSCC cells at 4-times higher CC 50 .…”
Section: Abstract Background/aim: Very Few Studies Of Anticancer Actmentioning
confidence: 99%
“…the ratio of mean CC 50 (HGF+HPLF+HPC) to mean CC 50 (Ca9-22+HSC-2+HSC-3+HSC-4), using seven cell lines [(D/B) in Table I] (19), and as the ratio of CC 50 (HGF) to CC 50 (Ca9-22) [(C/A) in Table I], using two cell lines derived from the gingival tissue (20). Normal keratinocytes, which are highly sensitive to many anticancer drugs (21), were not used in this study. Calculation of potency-selectivity expression (PSE).…”
Section: Calculation Of Tumor-specificity Index (Ts) Ts Was Calculatmentioning
confidence: 99%